Clinical, biochemical and genetic spectrum of 70 patients with ACAD9 deficiency: is riboflavin supplementation effective? - Repp, B; Mastantuono, E; Rötig, A; Poulton, J (BioMed Central, 2018)
Background: Mitochondrial acyl-CoA dehydrogenase family member 9 (ACAD9) is essential for the assembly of mitochondrial respiratory chain complex I. Disease causing biallelic variants in ACAD9 have been reported in individuals presenting with lactic acidosis and cardiomyopathy. Results: We describe the genetic, clinical and biochemical findings in a cohort of 70 patients, of whom 29 previously unpublished. We found 34 known and 18 previously unreported variants in ACAD9. No patients harbored biallelic loss of function mutations, indicating that this combination is unlikely to be compatible with life. Causal pathogenic variants were distributed throughout the entire gene, and there was no obvious genotype-phenotype correlation. Most of the patients presented in the first year of life. For this subgroup the survival was poor (50% not surviving the first 2 years) comparing to patients with a later presentation (more than 90% surviving 10 years). The most common clinical findings were cardiomyopathy (85%), muscular weakness (75%) and exercise intolerance (72%). Interestingly, severe intellectual deficits were only reported in one patient and severe developmental delays in four patients. More than 70% of the patients were able to perform the same activities of daily living when compared to peers. Conclusions: Our data show that riboflavin treatment improves complex I activity in the majority of patient-derived fibroblasts tested. This effect was also reported for most of the treated patients and is mirrored in the survival data. In the patient group with disease-onset below 1 year of age, we observed a statistically-significant better survival for patients treated with riboflavin.